Molecular distribution in intradermal injection for transfer and delivery of therapeutics - Lallow, Emran O.; Busha, Kishankumar J.; Park, Sarah H.; Atzampou, Maria; Jhumur, Nandita C.; Demiryurek, Yasir; Roberts, Christine C.; Shan, Jerry W.; Zahn, Jeffrey D.; Shreiber, David I.; Park, Young K.; Singer, Jonathan P.; et al. (Frontiers in Drug Delivery, 2023)
Intradermal (ID) injection is a technique widely used in laboratorial and clinical applications. The boundary of the dome-like bleb formed during injection is assumed to represent the lateral extent of the injected material. This work systematically characterizes cargo molecule distribution (puddle) as a function of injection volume and molecular/particle size in rat skin post ID injection. In general, results indicate that the puddle forms a subdomain laterally contained within the bleb, with an area inversely correlating to the molecular size of the injected material. For 50 μL and 100 µL injections, the average area of the bleb was 40.97 ± 6.30 mm2 and 55.64 ± 8.20 mm2, respectively, regardless of the molecular/particle size. On the other hand, the area of the puddle was dependent on the molecular size and ranged between 45.38 ± 8.29 mm2 and 6.14 ± 4.50 mm2 for 50 µL injections, and 66.64 ± 11.22 mm2 and 11.50 ± 9.67 mm2 for 100 µL injections. The lateral distribution appears to have no time-dependency up to 10 min post injection. The trend in the depth of cargo penetration is also similar, with smaller particles extending deeper into the dermis and subcutaneous fat layers. Because the area of puddle can be significantly less than that of the bleb, establishing base characterization is essential to understand cellular interactions with the injected biological substances.